Revision of the crab genus Garthambrus Ng, 1996, with the description of two new genera and discussion of the status of Tutankhamen Rathbun, 1925 (Crustacea: Brachyura: Parthenopidae) - Mclay, Colin L.; Tan, S. H. (Zootaxa, 2009)
The Indo-West Pacific genus Garthambrus Ng, 1996, is revised. Two new species are described from New Caledonia and French Polynesia. Lambrus (Parthenopoides) pteromerus Ortmann, 1893, is now transferred to Garthambrus. The genus now consists of 11 nominal species, viz. G. allisoni (Garth, 1992), G. cidaris (Garth and Davie, 1995), G. complanatus (Rathbun, 1906), G. lacunosus (Rathbun, 1906), G. posidon Ng, 1996, G. poupini (Garth, 1992), G. pteromerus (Ortmann, 1892), G. stellatus (Rathbun, 1906), G. tani Ahyong, 2008, G. darthvaderi sp. nov. and G. undulatus sp. nov. Although originally included in Garthambrus, Asterolambrus mironovi Zarenkov, 1990, is herein transferred to a new genus, Hispidolambrus gen nov. Most of these species are known from the West Pacific, but Garthambrus posidon only occurs in the Indian Ocean. Most specimens of Garthambrus have been collected from depths between 81–600 m. The monotypic Caribbean genus Tutankhamen Rathbun, 1925, which closely resembles Garthambrus, is also discussed. Heterocrypta epibranchialis Zarenkov, 1990, has some resemblance to Garthambrus but is here referred to a new genus, Zarenkolambrus, along with a new species, Z. minutus sp. nov.